Analysing Existence of Volatility Persistence in Sub-Sahara Africa Stock Markets - Peter Ifeanyichukwu Ali (AFRE (Accounting and Financial Review), 2019)
The aim of this paper was to analyse volatility persistence in Sub-Sahara stock markets. The study concentrated on selected markets including Ghana, Nigeria and South Africa by analysing univariate GARCH (1,1) model using monthly data from January 2000 to December 2017. Estimates from descriptive statistics show that the mean monthly returns are positive for the Sub-Sahara stock markets, but the South Africa stock market generates more returns than Nigeria and Ghana within the study period. Skewness coefficients show that the stock returns distributions of the Sub-Sahara Africa stock markets are negatively skewed. Excess kurtosis is positive for all the stock markets returns. The Jarque-Bera statistics indicate the stock markets’ series are not normally distributed. Unit roots tests results indicate that the Sub-Sahara Africa stock markets series are integrated of order one. The results of the GARCH (1,1) model provide evidence to show that the Sub-Sahara Africa stock markets exhibit volatility clustering and persistence. The study therefore concludes that there is volatility persistence in Sub-Sahara Africa Stock Markets. The study therefore recommends that Sub-Sahara Africa portfolio managers watch movements in stock market volatility as part of their portfolio management strategy and formulate cushion policies to mitigate effects of volatility shocks. DOI: https://doi.org/10.26905/afr.v2i1.3263